Interactive Computer - Simulation Strategy and Physics Performance of Grade 8 Students - Constante, Rhodel D; Agsalud, Priscilla L (ASEAN Multidisciplinary Research Journal, 2019)
This study investigated the effects of interactive computer-simulation strategy on Physics performance of Grade 8 students. The sample of the study constituted 80 Grade 8 students of Dr. Ramon De Santos National High School derived from two purposively selected classes. There were 33 students exposed in Interactive computer-simulation strategy (IC-SS) and 47 students were exposed to Traditional teaching strategy (TTS). Data of this study was collected using the Grade 8-Physics Achievement Test (G8-PAT) which utilized as a pre-test and post-test material. Descriptive and inferential statistics were used to test the null hypotheses of this study. This study revealed that Grade 8 students subjected in the study were mostly female, the majority had an outstanding and very satisfactory performance in Grade 7 Physics and most of the students had smartphones available at home. The result of this study revealed that the experimental and control group showed a respective increase in mean score from pre-test to post-test. However, the experimental group showed a greater mean difference of 12.21 compared to control group which had a mean difference of 9.06. In terms of performance level in post-test of Grade 8 students, the study revealed that most of the students in the experimental group had high (48.5%) performance level after exposure in IC-SS. While most of the students in the control group had an average (51.1%) performance level after exposure to TTS which is relatively lower compared to the experimental group. Overall, the study revealed that there is a significant difference in pre-test and post-test performance within groups based on Fc= 254.065 with a significance value of .000. Moreover, results of this study showed a significant difference in Physics performance of Grade 8 students between experimental group and control group based on Fc=17.586 with an associated significance value of .000. Results above implied that IC-SS is more effective in improving Physics performance of Grade 8 students compared to TTS. In addition, only profile sex of students exposed in IC-SS have significant relationship in Physics performance. Findings of the study strongly recommended that science teachers specifically the non-physics major shall adopt the use of Interactive Computer-Simulation in teaching Physics in Grade 8.